Diagnosis and management of TFE3-rearranged renal cell carcinoma: case report and literature review - Yongxin Zhang; Junxin Shen; Jinfeng Wu; Hongxing Huang; Fengjiao Meng; Runqiang Yuan; Yangbai Lu (BMC Urology)
Abstract Background TFE3-rearranged renal cell carcinoma is a rare malignancy with distinctive morphological and immunological characteristics. Although it can manifest in individuals of any age, its occurrence in adults is exceedingly uncommon, comprising only 1.5% of adult renal cell carcinomas. The disease typically presents with a benign course in pediatric patients, yet in adults, it often progresses rapidly and aggressively. Case presentation Herein, we present a case of a 35-year-old female diagnosed with TFE3-rearranged renal cell carcinoma, who was initially asymptomatic. Imaging studies revealed a solid renal mass in the left kidney without signs of metastasis. Initially misdiagnosed as a vascular smooth muscle lipoma, the patient underwent laparoscopic partial nephrectomy. Subsequent histopathological and molecular analyses validated the diagnosis of TFE3-rearranged renal cell carcinoma. The patient demonstrated favorable short-term outcomes after early laparoscopic intervention, with no evidence of tumor recurrence or metastasis at both the 4-month and 15-month follow-ups. Conclusions This case serves as a valuable resource for oncologists involved in the diagnosis and management of TFE3-rearranged renal cell carcinoma.